Do trees grow on money?: the implications of deforestation research for policies to promote REDD - Kanninen, M.; Murdiyarso, Daniel; Seymour, F.; Angelsen, A.; Wunder, Sven; German, L. (Center for International Forestry Research, 2007)
This paper has two objectives. First, it analyzes the past research on deforestation and summarizes the findings of that research, in terms of its relevance to the development of future REDD regimes. Second, it highlights areas where future research and methodological development are needed to support national and international processes on avoided deforestation and degradation.